A comparison of the antropological determinants for swimming and synchronized swimming in young female athletes - Dodigovic, L.; Sindik, J. (Sports Science and Health, 2015)
Swimming and synchronized swimming are two similar sports, but with main differences in specific structures of the movements in the synchronized swimming. This article attempts to provide an overview of the similarities and differences among young female athletes involved in these sports, primarily in the morphological characteristics of swimmers, as well as in the broader context of their functional capacity and motor characteristics. The distinctive features of the synchronized swimming in comparison with the traditional swimming are arising mainly due to the higher complexity of the technique of the movements in this sport.